The Armenian Genocide in the Kurdish Novel: Restructuring Identity through Collective Memory - Adnan Çelik; Ergin Öpengin (European Journal of Turkish Studies)
This article examines the recently increasing representation of the Armenian genocide and its aftermath in modern Kurdish literature in Turkey. This recent interest is argued to be nested within the “memory wave” in Turkey, but also motivated by both the pluralist ideological underpinnings of the dominant Kurdish movements in Turkey and a robust oral history transmission within Kurdish society. The memory of the genocide is shown to appear in Kurdish novels through a number of recurring themes, such as a nostalgic past cohabitation, Islamicized Armenians, and a redemptive continuity between Armenian and Kurdish suffering in consecutive decades. The article argues that the treatment of the genocide memory in Kurdish literature contributes to a wider-scale effort of establishing a non-negationist counter-memory, but that its potential for a genuine confrontation with the past is weakened by its selective treatment of the memory whereby issues of responsibility and guilt are often avoided.